2012
DOI: 10.1186/1471-2180-12-288
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus autoinducer-2 quorum sensing decreases biofilm formation in an icaR-dependent manner

Abstract: BackgroundStaphylococcus aureus is an important pathogen that causes biofilm-associated infection in humans. Autoinducer 2 (AI-2), a quorum-sensing (QS) signal for interspecies communication, has a wide range of regulatory functions in both Gram-positive and Gram-negative bacteria, but its exact role in biofilm formation in S. aureus remains unclear.ResultsHere we demonstrate that mutation of the AI-2 synthase gene luxS in S. aureus RN6390B results in increased biofilm formation compared with the wild-type (WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 70 publications
3
83
0
Order By: Relevance
“…3b). These results suggest that the defect of the pfs mutant strain in biofilm formation is not because of the disruption of AI-2, consistent with our previous studies showing that the S. aureus AI-2 reduces biofilm formation [22].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…3b). These results suggest that the defect of the pfs mutant strain in biofilm formation is not because of the disruption of AI-2, consistent with our previous studies showing that the S. aureus AI-2 reduces biofilm formation [22].…”
Section: Resultssupporting
confidence: 81%
“…The addition of in vitro-synthesized AI-2 did not restore the biofilm formation of the pfs mutant strain under either static or dynamic flow conditions, which suggest that the defect of the pfs mutant strain in biofilm formation is not because of the disruption of AI-2. In a previous study, we also showed that S. aureus AI-2 quorum-sensing reduces biofilm formation [22]. This means that pfs and AI-2 have opposite effect on biofilm formation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although biofilm formation under low-oxygen conditions was measured for many of the bacteria examined in this study (45)(46)(47)(48)(49), the new gasbag system allows measuring biofilm growth and physiology under gas conditions that are not easily attained using, for the most part, standard lab equipment. The gasbag system might also facilitate studies that are aimed at understanding the effect of oxygen therapy on microbial physiology and pathogenesis (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these enzymes are under the control of QS [71,72]. The cell dispersion process takes place through the QS that allows the formation of small agglomerates and a new biofilm formation [73].…”
Section: Bacterial Biofilm Productionmentioning
confidence: 99%